Relationship Between Adversity Quotient And Academic Stress In Muhammadiyah 9 Boarding School Smp Students: Hubungan Antara Adversity Quotient Dengan Stres Akademik Pada Peserta Didik Smp Muhammadiyah 9 Boarding School - Amelia Solikhah; Widyastuti (Academia Open, 2021)
Academic stress is an individual response that arises because of their inability to complete or complete academic demands. This study aims to determine the relationship between adversity quotient and academic stress in students of SMP Muhammadiyah 9 Boarding School Tanggulangin. This research is a correlational quantitative study. The population in this study were all students of SMP Muhammadiyah 9 Boarding School Tanggulangin, with a sample of 114 subjects. Data collection techniques in this study used the adversity quotient scale (ɑ = 0.949) and the academic stress scale (ɑ = 0.945). The data analysis technique used Pearson's product-moment correlation with the help of SPSS 18.0. The results of the research data analysis showed that the correlation coefficient (rxy) was -0.247 with a significance of 0.004 <0.05, meaning that there was a significant negative relationship between adversity quotient and academic stress in students of SMP Muhammadiyah 9 Boarding School Tanggulangin. In this study, the influence of the adversity quotient variable with academic stress was 6.1%.